Effect of educational intervention based on the PRECEDE-PROCEED model on preventive behaviors of cutaneous leishmaniasis among housewives - Ali Khani Jeihooni; Pooyan Afzali Harsini; Seyyed Mansour Kashfi; Tayebe Rakhshani
Leishmaniasis is an endemic disease in Iran. Since education to prevent the disease is important, this study aimed to determine the effect of educational intervention based on the PRECEDE-PROCEED model on preventive behaviors of cutaneous leishmaniosis among housewives. In this quasi-experimental study, 240 housewives under the coverage of health centers, who lived in the endemic area of Mianshahr, Fasa city, Fars Province, Iran in 2016, were selected (120 people for the experimental group and 120 for the control group). The educational intervention for the experimental group was based on the PRECEDE model, which consists of seven 50-60-minute sessions of lectures, group discussions, role playing, practical displays, and video and PowerPoint displays. These sessions addressed the familiarity with cutaneous leishmaniasis and its different types and carriers, methods of preventing and fighting against it, personal protection, sanitation of the environment and drinking water, spraying of sites, use of mosquito nets, etc. Data were collected before educational intervention and three months after educational intervention. The mean age of the experimental group was 39.24±9.12 years and that of the control group was 38.84±9.28 years. Three months after the intervention, the experimental group showed a significant increase in knowledge, attitudes, reinforcing factors, enabling factors, and performance compared to the control group. The education based on enabling factors, reinforcing factors, and predisposing factors had a significant effect on the preventive behaviors of cutaneous leishmaniasis among housewives.